Pesantren Raudhatul Jannah: Strategi Peningkatan Kemudahan Berusaha Dimasa Pandemi dengan Program-Program Pemberdayaan Keumatan - Widagda, Sidiq Pramana (Jurnal ABDIMAS PARIWISATA, 2021)
Pesantren Raudhatul Jannah: Strategies for Increasing Ease of Doing Business in the Pandemic Era with Public Empowerment Programs. The Tahfizh Raudhatul Jannah Islamic Boarding School is a picture of an institution that combines the spirit of education and entrepreneurship among its students. This entrepreneurial spirit also empowers the surrounding community by utilizing existing lands. This paper aims to describe the purpose and existence of the Tahfizh Raudhatul Jannah Islamic Boarding School and how the efforts of the Tahfizh Raudhatul Jannah Islamic Boarding School to exploit the existing potential of halal tourism and create various efforts to empower the surrounding community. The increase in Muslim tourists from year to year is an opportunity and a challenge for the tourism sector to develop halal tourism. Halal tourism development is carried out by creating a tour package program. Tourists must take part in activities at the pesantren so that they can memorize the Koran. This program makes Islamic boarding schools the centre of the economy by carrying out various business activities, ranging from raising catfish, goats, planting oranges and bananas.